Trailblazing Innovation Transformation Through Assistive Approaches for Inclusive Science Education - Gain, Ma. Germie F. (Future Science / FSH-PH Publications, 2025)
This study investigated the level of innovation in assistive technology (AT) among science teachers in inclusive classrooms, focusing on resource allocation and implementation, collabora-tion measures, technological training, personal professional ap-proach, and adaptability. Utilizing a mixed-methods approach, data were gathered from 36 science teachers through surveys and interviews. The results revealed a high level of innovation overall, with specific strengths and areas for improvement identi-fied.Teachers However, innovated resource allocation and imple-mentation to meet various student requirements. collaboration measures indicated average level of innovation, highlighting the need for systematic teacher collaboration and best practice ex-change. The high rating of technological training shows science teachers' proactive professional development to improve AT skills. Teachers' innovative personal professional approach fo-cused on lifelong learning and creative problem-solving to achieve inclusion. Teachers' adaptability to modify tools and cre-ate low-tech solutions for students also scored high, highlighting teachers' ability to modify existing tools and develop low-tech solutions to address specific student needs. The study identified key themes, including resource limitations, technological barriers, administrative and knowledge gaps, and student-centered chal-lenges, that influence teachers' innovative use of AT. Based on these findings, a comprehensive training workshop, STEAM AID, was proposed to equip teachers with the skills and knowledge needed to overcome these challenges and foster an inclusive learning environment.